ANALISIS PERAN APIP TERHADAP PROGRAM MONITORING CENTRE FOR PREVENTION KOORDINASI SUPERVISI PENCEGAHAN KORUPSI (MCP KORSUPGAH) KPK DALAM PENCEGAHAN KORUPSI - Sumarauw, David Charles; Manossoh, Hendrik; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2023)
This study aims at the understanding the role of APIP on the implementation and achievements of the MCP Korsupgah KPK program in preventing of corruption gacor5000. This research use qualitative methods through study case approach. By using agency theory, compliance theory and role model theory, the research results show that APIP's role in the implementation and achievements of the KPK's Korsupgah MCP program in prevention the corruption, become a partner of the KPK,become consulting and quality assurance for regional apparatur to fulfillment of documents of each indicator in the intervention area of ​​the MCP Korsupgah KPK's program by preparing an action plan, forming a monitoring and evaluation task force MCP review, increasing the competence of human resources inspectors and budget allocation adequate. The impact of the implementation of APBD budgeting for the right time, the procurement process up to the handover of work, the improvement of public services of the licensing process, increasing and controlling of regional owned assets, implementation of merit system in the promotion process, mutation, ASN rotation, the implementing of information technology-based innovations in optimization regional income through the creation of a tax database and in application of several applications such as e-samsat application, application-based audit through SPEKGAGA (Sistem Penilaian Kinerja Pengadaan Barang dan Jasa) to audit and monitoring all good activities physical realization of work and financial realization.